Characterizing Of Dual Focal Curves In D3 - Korpinar, Talat; Turhan, Essin; Bas, Selcuk (Soc Paranaense Matematica, 2013)
In this paper, we study dual focal curves in the Dual Lorentzian 3-space D-1(3). We characterize dual focal curves in terms of their dual focal curvatures.
Keywords: Frenet frame; Dual 3-space; Focal curve